How framing bias impacts preferences for innovation in bone tissue engineering - Laubach, Markus; Whyte, Stephen; Chan, Ho Fai; Hildebrand, Frank; Holzapfel, Boris Michael; Kneser, Ulrich; Dulleck, Uwe; Hutmacher, Dietmar W. (Tissue engineering, 2024)
It is currently unknown if surgeons and biomaterial scientists &or tissue engineers (BS&orTE) process and evaluate information in similar or different (un)biased ways. For the gold standard of surgery to move “from bench to bedside,” there must naturally be synergies between these key stakeholders’ perspectives. Because only a small number of biomaterials and tissue engineering innovations have been translated into the clinic today, we hypothesized that this lack of translation is rooted in the psychology of surgeons and BS&orTE. Presently, both clinicians and researchers doubt the compatibility of surgery and research in their daily routines. This has led to the use of a metaphorical expression “squaring of the circle,” which implies an unsolvable challenge. As bone tissue engineering belongs to the top five research areas in tissue engineering, we choose the field of bone defect treatment options for our bias study. Our study uses an online survey instrument for data capture such as incorporating a behavioral economics cognitive framing experiment methodology. Our study sample consisted of surgeons (n = 208) and BS&orTE (n = 59). And we used a convenience sampling method, with participants (conference attendants) being approached both in person and through email between October 22, 2022, and March 13, 2023. We find no distinct positive-negative cognitive framing differences by occupation. That is, any framing bias present in this surgical decision-making setting does not appear to differ significantly between surgeon and BS&orTE specialization. When we explored within-group differences by frames, we see statistically significant (p < 0.05) results for surgeons in the positive frame ranking autologous bone graft transplantation lower than surgeons in the negative frame. Furthermore, surgeons in the positive frame rank Ilizarov bone transport method higher than surgeons in the negative frame (p < 0.05).
Gesehen am 04.11.2024